The Topmetal-CEE prototype, a direct charge sensor for the beam monitor of the CSR external-target experiment. (27th September 2022) - You, B.; Gao, C.; Yang, P.; Guo, D.; Tian, X.; Huang, G.; Liu, J.; Sun, X.; Wang, H.; Xiao, L.; Huang, F.; Feng, W.; et al.
Abstract: The Cooler-Storage-Ring External-target Experiment (CEE) which is being constructed since 2020 is a spectrometer to study the properties of nuclear matter at high baryon density region. We present the design and simulation results of a sensor named Topmetal-CEE which is being developed for an online beam monitor of the CEE. A prototype of the Topmetal-CEE has been designed in a standard CMOS 130 nm process and is being fabricated. The Topmetal-CEE prototype has 180 channels with a pitch of 100 μm. In each channel, electrons are collected by a charge collection electrode which is a top-most metal exposed to the surrounding media, amplified by a charge sensitive amplifier, and then fed into a discriminator. The output of the discriminator is split into two paths which record Time of Arrival (ToA) and Time over Threshold (ToT) of the collected signal, respectively. In order to reduce the dead time, 180 channels are split into two separate parts and then the information in each part is read out by a data-driving priority readout scheme independently. Each channel has its own address encoded by an address encoder. The ToA, ToT and address of each channel are framed and encoded, and then transferred off chip with a serial speed of 4.4 Gbps.